Fair Data, Bayesian Statistics and Human Cohort Studies: Current Trends in Metabolomic Research - Oliver Fiehn (Metabolites)
This Special Issue was published to celebrate 10+ years of research and services at the UC Davis West Coast Metabolomics Center (WCMC) [...]